Pemberdayaan Pelaku Usaha Konveksi Dengan Teknik Pemasaran Media Sosial Di Jurangmangu, Tangerang Selatan - Irfal; Ervina Taviprawati; Rahmat Ingkadijaya (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2024)
The aim of this outreach is to teach convection business actors how to effectively use social media for marketing, including creating interesting content and using advertising, in order to expand audience reach and increase sales. This activity was held at the Tourism Institute Campus with 10 convection business actors from Jurangmangu, South Tangerang, and included three stages: theoretical and practical discussion sessions at participant locations, direct training on campus about social media, and mentoring and consultation for the application of knowledge and provision of materials training. The results of the activity showed that participants felt that social media marketing education was very effective and relevant, provided clear understanding, and was useful in improving their skills in marketing products conventionally via social media. All participants felt confident and recommended this counseling to other convection business actors.